2017
DOI: 10.1111/hepr.12850
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide‐enhanced magnetic resonance imaging is useful in predicting malignant potential of vascular transformation of hypointense hypovascular nodules on gadoxetic acid‐enhanced magnetic resonance imaging

Abstract: Superparamagnetic iron oxide-enhanced MRI is useful for predicting the malignant potential of vascular transformation of hypovascular nodules with hypointensity observed in the HBP on Gd-EOB-DTPA-enhanced MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Despite the results that Ferumoxides has been withdrawn from the market, research on Ferucarbotran (Resovist ® ) and recently ferumoxytol are still being pursued during the last 5 years, particularly on GBCA and SPIO double contrast, and texture analysis for enhanced MR images for hepatic fibrosis evaluation (126)(127)(128)(129) (Figure 13). Maurea et al (130) suggested that Ferucarbotran enhanced MRI provides a diagnostic incremental value, particularly to characterize focal liver lesions compared to Gd-DTPA enhanced MR; they recommend the use of SPIO when liver lesion characterization is requested and Gd-DTPA enhanced MR images are uncertain (Figures 14-16).…”
Section: Spio Enhanced Liver Mrimentioning
confidence: 99%
“…Despite the results that Ferumoxides has been withdrawn from the market, research on Ferucarbotran (Resovist ® ) and recently ferumoxytol are still being pursued during the last 5 years, particularly on GBCA and SPIO double contrast, and texture analysis for enhanced MR images for hepatic fibrosis evaluation (126)(127)(128)(129) (Figure 13). Maurea et al (130) suggested that Ferucarbotran enhanced MRI provides a diagnostic incremental value, particularly to characterize focal liver lesions compared to Gd-DTPA enhanced MR; they recommend the use of SPIO when liver lesion characterization is requested and Gd-DTPA enhanced MR images are uncertain (Figures 14-16).…”
Section: Spio Enhanced Liver Mrimentioning
confidence: 99%
“…To meet the challenge of developing a safe, convenient, and highly effective dual-mode imaging agent to diagnose HF, we chose SPIO and ICG as the photographic developers for T2 MRI and NIR imaging, respectively, which have been in clinical use for a long time. 30,31 Compared with the conventional diagnostic method, NIR imaging and MRI could offer high sensitivity and spatial resolution for the early detection of HF with no radiation exposure, and could be a powerful tool for offering structural and functional imaging information. The high sensitivity of NIR imaging enabled detection of tiny amounts of ICG.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Superparamagnetic iron oxide (SPIO) nanoparticles have low toxicity, high sensitivity and excellent biocompatibility, and are the rst T2 contrast agents for MRI to be used clinically. 30 Compared with uorescent quantum dots and cyanine dye, indocyanine green (ICG) is the only NIR organic dye approved by the US Food and Drug Administration (FDA) for medical imaging and diagnosis in clinical practice for more than 50 years. 31 ICG and SPIO have disadvantages: a tendency to aggregate and degrade rapidly in aqueous solution; a tendency to clear rapidly from the body with a short half-life of 2-4 min; absence of active targeting; being prone to photo-bleaching.…”
Section: Introductionmentioning
confidence: 99%